The Comparison of The Influence of Intellectual Capital, Managerial Ownweship, Institutional Ownership and Corporate Social Responsibility on Company Financial Performance - Patricia Manasye Tiurma; Rilla Gantino (INTERNATIONAL JOURNAL OF TRENDS IN ACCOUNTING RESEARCH, 2020)
This study aims to compare the effect of intellectual capital, managerial ownership, institutional ownership and corporate social responsibility on the financial performance of coal mining sub-sectors and infrastructure sub-sectors. The samples used are all sub-sector coal mining companies and infrastructure sub-sectors which are listing year 2014-2018 on www.idx.co.id website using nonprobability sampling method with a census technique sampling which is the number of samples used are 37 coal mining and infrastructure subsector companies. The analytical method used is multiple regression. The results of hypothesis testing show that intellectual capital, managerial ownership, institutional ownership and corporate social responsibility have a significant effect jointly on ROA and ROE of coal mining sub-sector companies, but does not significantly affect the company's ROE sub-sector infrastructure. Partially, managerial ownership affects insignificant financial performance in both sectors. Meanwhile, institutional ownership of coal mining companies has significant effect on ROA, but the effect is insignificant to the ROE and has no significant effect on the ROA and ROE infrastructure companies. Corporate social responsibility has a partially insignificant effect on ROA and ROE in the coal mining sub-sector, but has a negative and significant effect on ROA in the infrastructure sub-sector.